Additional Language Learning in Montessori settings: insights from the implementation process of a Second Language Programme in a Scottish Montessori school - Romali Rosales Chavarría (Problemy Wczesnej Edukacji)
Very little has been published academically on language learning within Montessori education. This is a field that has grown and evolved from the ground as schools face the need to include additional language learning and develop bilingual programmes as part of their curricula. This article reports on the research findings of an action research exploratory study in a Montessori school in Scotland, which was a follow-up to a three-year action research inquiry in Mexico into the development of a second language programme in a Montessori setting. It shows how another target language in a different national context influences how an implementation process is shaped and some of the factors that come into play. Results are presented considering four phases spread in four school years with the experimentation and strategies used and trialled during this time across school levels. It shows different ways to integrate additional languages into the Montessori learning environment that correspond to strong and weak bilingual programmes (Baker 2001) and some of the factors that influence an effective implementation such as continuity, consistency, and alignment with a school’s needs and priorities among others. Language Learning programmes in Montessori settings need to be considered from the perspective of the child, the teachers, the parents and the school as they all integrate to create tailor made bilingual programmes that respond to the context, characteristic and resources of the school.